4
$\begingroup$

This question is inspired by the MO query here, although it has no direct implications.

Define the family of polynomial functions $$f_n(x)=n^2x^{n-1}-\frac{d}{dx}\left(\frac{x^n-1}{x-1}\right),$$ and the associated family of algebraic functions $$g_n(x)=\frac{\sqrt{f_n(x)}}n+\sum_{j=1}^{n-1}\frac{\sqrt{f_j(x)}}{j(j+1)}.$$

Question. Despite the complicated expressions for $f_n$ and $g_n$, does $$h_n(x)=\sum_{k=0}^n\left(g_n(x)-g_k(x)\right)^2$$ have a neat (closed) formula?

UPDATE. user64494 (see below) has found $h_n(x)=nx^{n-1}$. Any proof?

Convention: $g_0:=0$ and empty sums are zero.

For example, $h_2(x)=g_2(x)^2+(g_2(x)-g_1(x))^2+(g_2(x)-g_2(x))^2=2x$.

$\endgroup$
6
  • $\begingroup$ Do you want to start that last sum at $k=1$? $g_0$ doesn't exist. $\endgroup$ – Robert Israel Jan 29 '17 at 4:45
  • $\begingroup$ Good point. Edited. $\endgroup$ – T. Amdeberhan Jan 29 '17 at 11:48
  • $\begingroup$ A huge closed-form expression for $h_N(x)$ (obtained with Maple) can be seen here dropbox.com/s/kv0r1zemuu284kt/sum.pdf?dl=0 . It is not nice. I didn't succeed to obtain its asymptotics as $N\to\infty$. $\endgroup$ – user64494 Jan 29 '17 at 15:03
  • $\begingroup$ Here dropbox.com/s/0cpub4nd8xp5yxm/small%20sums.pdf?dl=0 it is. However, the result is discouraged. $\endgroup$ – user64494 Jan 29 '17 at 15:22
  • $\begingroup$ You are missing $k=0$ in the sum for $h_N(x)$. The term is $g_N(x)^2$. $\endgroup$ – T. Amdeberhan Jan 29 '17 at 15:45
3
$\begingroup$

A large part of the result doesn't really depend on $f_n$. For an arbitrary sequence $(a_n)$, define two sequences by $G_0=0$, $H_0=0$, and for $n\ge1$, $$G_n=\frac{a_n}{n}+\sum_{j=1}^n{\frac{a_j}{j(j+1)}}\quad\text{and}\quad H_n=\sum_{k=0}^n{(G_n-G_k)^2}.$$ Then $$H_{n+1}-H_n=G_{n+1}^2-G_n^2+\sum_{k=1}^n{(G_{n+1}-G_n)(G_{n+1}+G_n-2G_k)}.$$ The right-hand side simplifies to $$(G_{n+1}-G_n)\big((n+1)(G_{n+1}+G_n)-2\sum_{k=1}^n{G_k}\big),$$ where the last sum simplifies a lot: $$\sum_{k=1}^n{G_k}=(n+1)\sum_{j=1}^n{\frac{a_j}{j(j+1)}}$$ so that in the end everything telescopes and $$H_{n+1}-H_n=\frac{1}{n+1}(a_{n+1}^2-a_n^2).$$ Applying this with $a_n=\sqrt{f_n(x)}$ gives $$h_{n+1}(x)-h_n(x)=\frac{1}{n+1}(f_{n+1}(x)-f_n(x))=\frac{1}{n+1}\left((n+1)^2x^n-n^2x^{n-1}-\frac{d}{dx}\left(\frac{x^{n+1}-x^n}{x-1}\right)\right)= \frac{1}{n+1}\left((n+1)^2x^n-n(n+1)x^{n-1}\right)=(n+1)x^n-nx^{n-1},$$ whence the proof by induction.

$\endgroup$
1
  • $\begingroup$ Very nice idea to look at $H_{n+1}-H_n$. Introducing a difference to pull out a common factor and get a lot of unexpected(?) telescoping offered later - would you believe it? :) $\endgroup$ – Wolfgang Jan 31 '17 at 10:15
3
$\begingroup$

The results of the Mathematica's code

f := Function[{n, x}, n^2*x^(n - 1) - D[(x^n - 1)/(x - 1), x]]
g := Function[{n, x},Sqrt[f[n, x]]/n + Sum[Sqrt[f[j, x]]/(j*(j + 1)), {j, 1, n - 1}]]
n = 60; FullSimplify[ g[n, x]^2 + Sum[(g[n, x] - g[k, x])^2, {k, 1, n}]]

60 x^59

n = 34; FullSimplify[g[n, x]^2 + Sum[(g[n, x] - g[k, x])^2, {k, 1, n}]]

34 x^33

suggest the answer $nx^{n-1}$. The same result is obtained with Maple 2016 through

restart; f := (n, x)-> n^2*x^(n-1)-(diff((x^n-1)/(x-1), x)):
g := (n, x) -> sqrt(f(n, x))/n+sum(sqrt(f(j, x))/(j*(j+1)), j = 1 .. n-1) :
simplify(expand([seq(sum((g(N, x)-g(k, x))^2, k = 1 .. N)+g(N, x)^2, N = 1 .. 5)]));

[1, 2*x, 3*x^2, 4*x^3, 5*x^4]

$\endgroup$
1
  • $\begingroup$ Great! Now, we need a proof. $\endgroup$ – T. Amdeberhan Jan 29 '17 at 20:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.